2021
DOI: 10.1016/j.kisu.2020.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Iron metabolism and management: focus on chronic kidney disease

Abstract: Anemia is common in patients with chronic kidney disease (CKD) and results from the dysregulation of iron metabolism and erythropoiesis. Hepcidin is a key regulator of iron availability and leads to iron sequestration during the state of iron repletion. Decreases in the level of hepcidin in the presence of hypoxia and/or iron limitation allow for greater iron availability for erythropoiesis. However, kidney excretion of hepcidin decreases as the severity of CKD increases, whereas production of hepcidin is incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 110 publications
(131 reference statements)
1
20
0
2
Order By: Relevance
“…The results showed that HD patients have a high significant (p=0.0001) increase in mean of serum Hepcidin level of (622.3±139.6) pg/ml, as compared with the controls group about (465.16±80.31) pg/ml, Figure (1). Furthermore, hepcidin levels exhibited a significant (p< 0.05) increase in 37% of HD patients with severe anemia about (692.4±119.8) pg/ml more than patient with 49.2% of moderate about (605.3±117.7) pg/ml, (p=0.007) as compared with 13.8% of mild anemia groups (531.8±99.12) pg/ml, (p=0.001), but no significant between mild and moderate anemia groups (p=0.099), Figure (2).…”
Section: Serum Hepcidin Levelsmentioning
confidence: 90%
See 2 more Smart Citations
“…The results showed that HD patients have a high significant (p=0.0001) increase in mean of serum Hepcidin level of (622.3±139.6) pg/ml, as compared with the controls group about (465.16±80.31) pg/ml, Figure (1). Furthermore, hepcidin levels exhibited a significant (p< 0.05) increase in 37% of HD patients with severe anemia about (692.4±119.8) pg/ml more than patient with 49.2% of moderate about (605.3±117.7) pg/ml, (p=0.007) as compared with 13.8% of mild anemia groups (531.8±99.12) pg/ml, (p=0.001), but no significant between mild and moderate anemia groups (p=0.099), Figure (2).…”
Section: Serum Hepcidin Levelsmentioning
confidence: 90%
“…The statistical analysis in the Table (1) indicated to 90 samples consisted of 65 HD patients with median (IQR) dialysis vintage was (12 (3-36) month, compared with 25 healthy participates as control group. No significant differences in the mean ages of the HD patients were (45.65±13.34) compared to control groups were (50±12.73) year, (p=0.164).…”
Section: Demographic and Clinical Characteristics Of Hemodialysis (Hd...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hepcidin, a peptide produced in the liver, was discovered in 2000 and is the key regulator of iron use, recycling, and transport. 19 , 20 , 21 Its physiologic role is to protect the organism against iron overload and to sequester iron in storage sites in the presence of infection by siderophilic pathogens. Hepcidin synthesis is stimulated by inflammation and increased storage iron and is decreased by iron deficiency and erythropoiesis.…”
Section: Anemia In Ckd: Prevalence and Pathophysiologymentioning
confidence: 99%
“…The main causes of anemia are: reduced production of erythropoietin (EPO), which stimulates the production of erythrocytes (Bueno & Frizzo, 2014;Naini et al, 2015;Oliveira et al, 2019;Agarwal, 2021), deficiency of iron, inflammation, and vitamin D axis deficiencies (Zughaier et al, 2014;Bacchetta et al, 2014;Lima, 2017;Al-shaer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%